Preparation method of copper-based catalyst capable of realizing industrial ampere-level current density as well as product and application of copper-based catalyst
Through hydrothermal and calcining treatment of copper salts and alkaline substances, a copper-based catalyst with excellent electrocatalytic properties was prepared, which solved the problem of carbonate deposition and low efficiency of C2+ products in electrocatalytic CO2 reduction reaction, and achieved the following: High-efficiency electrical reduction CO conversion at industrial ampere current density.
Patent Information
- Application Number
- CN202411617457.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The prior art has problems of carbonate deposition and low efficiency of C2+ products in electrocatalytic CO2 reduction reactions, especially competitive hydrogen evolution reactions that are prone to occur under large current density, resulting in a decrease in the selectivity and stability of the catalyst.
The copper salt and alkaline substance are dissolved to form a mixed solution. After hydrothermal treatment and calcination treatment, a copper-based catalyst with a block structure and a sponge-like nanopore structure is prepared.
It realizes efficient electrical reduction CO conversion at industrial ampere current density, with the Faraday efficiency of H2 less than 2%, and the Faraday efficiency of C2+ products greater than 97%, meeting the requirements of industrial applications.
Smart Images

Figure CN119465238A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material synthesis and electrocatalysis, and in particular to a preparation method of a copper-based catalyst capable of achieving industrial ampere-level current density, and a product and application thereof. Background Art
[0002] Excessive emissions of greenhouse gases such as carbon dioxide (CO2) have caused increasingly serious environmental problems. Solving the CO2 problem will help alleviate energy problems and produce chemicals with high added value.
[0003] Compared with traditional thermal catalytic CO2, the electrocatalytic reduction of CO2 (CO2RR) can directly use water as a hydrogen source and realize the co-electrolytic reduction of CO2 and H2O under mild conditions through renewable electricity, which is very important in producing high energy density and high added value multi-carbon (C 2+ ) products. In order to avoid the carbonate deposition (2OH – +CO2=CO3 2– +H2O) and C 2+ The product has low Faraday efficiency. Currently, research is beginning to gradually convert CO2–C 2+ The reduction reaction is divided into two steps. Carbon monoxide (CO) produced from CO2 is used as raw material, and then converted into C 2+ The use of gas diffusion electrodes (GDEs) has increased the current density of CO2RR / CORR from tens of milliamperes per square centimeter to hundreds of milliamperes today. However, the competitive hydrogen evolution reaction (HER) is more likely to occur at high current densities, which often reduces the selectivity and stability of the catalyst and causes a loss of energy efficiency. Therefore, the development of cheap, energy-efficient catalysts for the electrochemical conversion of CO at industrial ampere-level current densities and that can suppress HER is the key to industrial scalability.
[0004] Copper and its compounds are still the most effective materials for electroreduction of CO to C. 2+ The copper catalyst has a moderate adsorption energy for *CO and is conducive to the hydrogenation and C-C coupling reaction of *CO intermediates (ChemPhysChem, 2017, 18, 3266-3273). For example, a Chinese patent with publication number CN115490258A discloses a copper oxide nanosheet catalyst. The copper oxide nanosheet obtained by the preparation method is effective for the electrocatalytic conversion of CO2 / CO to C 2+The Faraday efficiency of the product can reach 85%. How to achieve low hydrogen evolution Faraday efficiency and efficient electro-reduction CO conversion capacity at industrial ampere current density often depends on the inherent properties of the catalyst. For example, a polycrystalline copper nanomaterial mentioned in the Chinese patent publication number CN113913932A has a high Faraday efficiency of 0.9A cm -2 The current density is about 70% C 2+ Faraday efficiency. The copper-palladium alloy nanoparticle catalyst prepared by the Chinese patent with publication number CN113881955A can -2 The Faradaic efficiency of acetic acid reached 70% at the current density, but did not reach the industrial ampere level test conditions.
[0005] Although copper-based catalysts have significant advantages in the electroreduction of CO to produce C 2+ performance, but can it operate at industrial ampere current density and maintain C 2+ Excellent selectivity of the product is still the key to be developed urgently. Therefore, developing a copper-based catalyst with simple synthesis method, rapid preparation, ampere-level current density operation conditions and excellent performance is of great significance for industrial scalability. Summary of the invention
[0006] The object of the present invention is to provide a preparation method of a copper-based catalyst capable of achieving an industrial ampere-level current density, and a product and application thereof. The preparation method is simple and efficient, and the prepared copper-based catalyst has a high active CO electroreduction ability when applied at an industrial ampere-level current density.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a copper-based catalyst capable of achieving industrial ampere-level current density, the method comprising the following steps:
[0009] (1) dissolving a copper salt and an alkaline substance to form a mixed solution;
[0010] (2) subjecting the mixed solution obtained in step (1) to hydrothermal treatment to obtain a copper precursor;
[0011] (3) The copper precursor prepared in step (2) is calcined to obtain a copper-based catalyst.
[0012] The invention uses alkaline substances as precipitants, forms metal compounds through simple hydrothermal treatment, and converts the metal copper compounds into copper-based catalysts with excellent performance through calcination treatment.
[0013] The copper salt of the present invention includes a mixture of one or more inorganic copper salts such as copper nitrate, copper sulfate, copper acetate, copper chloride, etc.
[0014] Preferably, the copper salt is copper nitrate and copper chloride, and more preferably copper nitrate.
[0015] The alkaline substance of the present invention can be a mixture of one or more alkaline substances such as ammonia water, urea, ammonium fluoride, ammonium bifluoride, sodium hydroxide, potassium hydroxide, etc.
[0016] Preferably, the alkaline substance is urea and ammonium fluoride, and more preferably urea.
[0017] The molar ratio of the copper salt to the alkaline substance of the present invention is 1.0:1.0-15.0.
[0018] Preferably, the molar ratio of the copper salt to the alkaline substance is 1.0:2.0 to 6.0. More preferably, the molar ratio of the copper salt to the alkaline substance is 1.0:2.0 to 5.0.
[0019] The hydrothermal treatment temperature of the present invention is 80-200°C.
[0020] Preferably, the hydrothermal temperature is 100 to 180°C, more preferably 120 to 140°C.
[0021] The hydrothermal treatment time of the present invention is 8 to 24 hours.
[0022] Preferably, the hydrothermal treatment time is 10 to 16 hours, more preferably 12 to 14 hours.
[0023] The copper precursor calcination temperature of the present invention is 300-600°C.
[0024] Preferably, the calcination temperature is 400-500°C, more preferably 450°C.
[0025] The copper precursor calcination time of the present invention is 4 to 12 hours.
[0026] Preferably, the calcination time is 5 to 8 hours, more preferably 6 hours.
[0027] The present invention also provides a copper-based catalyst obtained according to the above preparation method.
[0028] The copper-based catalyst body presents a block structure, and a sponge-like nano-pore structure exists on the surface.
[0029] The present invention also discloses the application of the copper-based catalyst in the electro-reduction reaction of CO. The application is the electro-reduction reaction of CO at an industrial ampere-level current density.
[0030] The catalyst can be directly used for the electroreduction of CO to produce C 2+ The product does not need to be treated by other means. The catalyst shows excellent electrocatalytic performance in the range of 0.1 to 1.1 A cm -2 In the current density range, the Faradaic efficiency of H2 is less than 2%, and C 2+ The Faradaic efficiency of the product is greater than 97%. -2 In the current density range, C 2+ The Faradaic efficiency of the products is maintained above 90%, meeting the requirements of industrial ampere-level application current density.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] In the present invention, a copper-based material capable of achieving an industrial ampere-level operating current density can be prepared as a catalyst by simple hydrothermal and calcination, and the preparation process is simple, controllable, and has a wide range of raw material sources, low cost, environmental friendliness, and can be prepared in large quantities, so that it is suitable for industrial production; the copper-based catalyst provided by the present invention exhibits excellent electrocatalytic reduction of CO activity and stability, and the catalyst still exhibits excellent electrocatalytic performance in the electrocatalytic reduction of CO reaction at an ampere-level current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope (SEM) image of the copper-based catalyst prepared in Example 1.
[0034] Figure 2 This is the X-ray diffraction spectrum XRD pattern of the copper-based catalyst prepared in Example 1.
[0035] Figure 3 This is a scanning electron microscope (SEM) image of the copper-based catalyst prepared in Example 2.
[0036] Figure 4 This is the X-ray diffraction spectrum XRD pattern of the copper-based catalyst prepared in Example 2.
[0037] Figure 5 This is a graph showing the electro-reduction CO reaction performance of the copper-based catalyst prepared in Example 1.
[0038] Figure 6 This is a diagram showing the stability of the device-based large-area CO electroreduction reaction of the copper-based catalyst prepared in Example 1.
[0039] Figure 7 This is the performance diagram of the electro-reduction CO reaction of the copper-based catalyst prepared in Example 2. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0041] The raw materials used in the following specific embodiments are all purchased from the market.
[0042] Example 1
[0043] (1) Dissolve copper nitrate and urea in 50 mL of deionized water at a molar ratio of 1.0:2.0 and stir evenly;
[0044] (2) transferring the mixed solution obtained in step (1) to a hydrothermal reactor and performing a hydrothermal reaction at 140° C. for 6 h, cooling the hydrothermal reactor, and centrifuging and drying the precipitate to obtain a copper precursor;
[0045] (3) The copper precursor prepared in step (2) is calcined in a muffle furnace at 450° C. for 6 h to obtain a copper-based catalyst that can achieve an industrial ampere-level current density.
[0046] Figure 1 The SEM image of the copper-based catalyst synthesized in Example 1 is shown in FIG. Figure 1 It can be seen that the catalyst body presents a block structure, and there is a sponge-like nanopore structure on the surface.
[0047] Figure 2 The X-ray diffraction spectrum XRD diagram of the copper-based catalyst synthesized in Example 1 is as follows: Figure 2 It can be seen that the characteristic peaks of the catalyst belong to the XRD diffraction peaks of copper oxide.
[0048] Example 2
[0049] (1) Dissolve copper sulfate and ammonium fluoride in 50 mL of deionized water at a molar ratio of 1.0:5.0 and stir evenly;
[0050] (2) transferring the mixed solution obtained in step (1) to a hydrothermal reactor and performing a hydrothermal reaction at 120° C. for 12 h, cooling the hydrothermal reactor, and centrifuging and drying the precipitate to obtain a copper precursor;
[0051] (3) The copper precursor prepared in step (2) is calcined in a muffle furnace at 450° C. for 6 h to obtain a copper-based catalyst that can achieve an industrial ampere-level current density.
[0052] Figure 3 The SEM image of the copper-based catalyst synthesized in Example 2 is shown in FIG. Figure 3 It can be seen that the catalyst body presents a block structure, and there is a sponge-like nanopore structure on the surface.
[0053] Figure 4 The X-ray diffraction spectrum XRD diagram of the copper-based catalyst synthesized in Example 2 is as follows: Figure 4 It can be seen that the characteristic peaks of the catalyst belong to the XRD diffraction peaks of copper oxide.
[0054] Example 3
[0055] (1) Dissolve copper nitrate and ammonia water in 50 mL of deionized water at a molar ratio of 1.0:3.0 and stir evenly;
[0056] (2) transferring the mixed solution obtained in step (1) to a hydrothermal reactor and performing a hydrothermal reaction at 130° C. for 12 h, cooling the hydrothermal reactor, and centrifuging and drying the precipitate to obtain a copper precursor;
[0057] (3) The copper precursor prepared in step (2) is calcined in a muffle furnace at 450° C. for 6 h to obtain a copper-based catalyst that can achieve an industrial ampere-level current density.
[0058] Application Example 1
[0059] Example 1 Preparation of C by electroreduction of CO 2+ Product cathode material:
[0060] (1) Weigh 20 mg of the copper-based catalyst prepared in Example 1 using an analytical balance, then add 900 μL of anhydrous ethanol and 100 μL of a 0.5 wt.% Nafion solution, and perform ultrasonic treatment for 2 h to obtain a uniformly dispersed catalyst slurry;
[0061] (2) Using a spray gun, the mixed catalyst slurry is evenly sprayed onto YLS-30T conductive carbon paper, and the carbon paper is heated and dried during the spraying process;
[0062] (3) Using Ag / AgCl as the reference electrode and nickel foam as the reaction counter electrode, the electrochemical performance test was carried out in a flow electrolytic cell. The copper-based catalyst prepared in Example 1 was used as the reaction working electrode. The effective area of the electrode was 1.0×1.0 cm 2 1.0 mol / L potassium hydroxide was used as the electrolyte, CO gas was continuously introduced, and then the electroreduction CO performance was tested at different current densities. The gas phase product was analyzed by gas chromatography, and the liquid phase product was analyzed by 1 H NMR spectroscopy (600 MHz).
[0063] Figure 5This is the performance diagram of the electro-reduction CO reaction of the copper-based catalyst prepared in Example 1. -2 In the current density range, the Faradaic efficiency of H2 is less than 2%, and C 2+ The Faradaic efficiency of the product is greater than 97%. -2 In the current density range, C 2+ The Faradaic efficiency of the products is maintained above 90%, meeting the requirements of industrial ampere-level application current density.
[0064] The copper-based catalyst prepared by the present invention was tested on a device using a membrane electrode with a two-electrode system (effective electrode area is 100 cm 2 ), with a titanium mesh loaded with iridium trioxide as the reaction anode. The current and potential of the reaction system were controlled by a DC power supply. Under a total current of 20A, the copper-based catalyst synthesized by the present invention was stable for 120 minutes ( Figure 6 ), can maintain a high C 2+ The product selectivity and electrochemical stability are excellent, and the application prospects are broad.
[0065] Application Example 2
[0066] Example 2 Preparation of C by Electroreduction of CO 2+ Product cathode material:
[0067] (1) Weigh 20 mg of the copper-based catalyst prepared in Example 2 using an analytical balance, then add 900 μL of anhydrous ethanol and 100 μL of a 0.5 wt.% Nafion solution, and perform ultrasonic treatment for 2 h to obtain a uniformly dispersed catalyst slurry;
[0068] (2) Using a spray gun, the mixed catalyst slurry is evenly sprayed onto YLS-30T conductive carbon paper, and the carbon paper is heated and dried during the spraying process;
[0069] (3) Using Ag / AgCl as the reference electrode and nickel foam as the reaction counter electrode, the electrochemical performance test was carried out in a flow electrolytic cell. The copper-based catalyst prepared in Example 2 was used as the reaction working electrode. The effective area of the electrode was 1.0×1.0 cm 2 1.0 mol / L potassium hydroxide was used as the electrolyte, CO gas was continuously introduced, and then the electroreduction CO performance was tested at different current densities. The gas phase product was analyzed by gas chromatography, and the liquid phase product was analyzed by 1 H NMR spectroscopy (600 MHz).
[0070] Figure 7 This is the performance diagram of the electro-reduction CO reaction of the copper-based catalyst prepared in Example 2.-2 In the current density range, C 2+ The Faradaic efficiency of the products is maintained above 90%, meeting the requirements of industrial ampere-level application current density.
Claims
1. A method for preparing a copper-based catalyst capable of achieving industrial ampere-level current density, characterized in that: The preparation method comprises the following steps: (1) dissolving a copper salt and an alkaline substance to form a mixed solution; (2) subjecting the mixed solution obtained in step (1) to hydrothermal treatment to obtain a copper precursor; (3) The copper precursor prepared in step (2) is calcined to obtain a copper-based catalyst.
2. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The copper salt in step (1) is an inorganic copper salt, selected from a mixture of one or more of copper nitrate, copper sulfate, copper acetate or copper chloride.
3. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The alkaline substance in step (1) is selected from a mixture of one or more of urea, ammonia water, ammonium fluoride, ammonium bifluoride, potassium hydroxide or sodium hydroxide.
4. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The molar ratio of the copper salt to the alkaline substance in step (1) is 1.0:1.0-15.
0.
5. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step (2) is 80 to 200° C. and the time is 8 to 24 hours.
6. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The copper precursor is calcined at a temperature of 300 to 600° C. and for a time of 4 to 12 hours in step (3).
7. A copper-based catalyst obtained according to the preparation method according to any one of claims 1 to 6.
8. The copper-based catalyst according to claim 7, characterized in that The copper-based catalyst body presents a block structure, and a sponge-like nano-pore structure exists on the surface.
9. Use of the copper-based catalyst according to claim 7 in an electro-reduction reaction of CO.
10. The use according to claim 9, characterized in that: The application is to produce multi-carbon products by electro-reduction of CO at industrial ampere-level current density.
Citation Information
Patent Citations
Electrocatalyst for generating acetic acid through electrocatalytic reduction of carbon monoxide, and application thereof
CN113881955A
Polycrystalline copper nano material, and preparation method and application thereof
CN113913932A
Preparation method of copper oxidechemically modified electrode for detecting glucose
CN106896151A
Flaky nano copper oxide as well as preparation method and application thereof
CN114763268A
Copper oxide nanosheet and preparation method thereof, and method for preparing ammonia through electro-catalysis of nitrate
CN115196665A
Cited By
Preparation method and application of aluminum modified copper-based catalyst
CN120519901A
Preparation method and application of aluminum-modified copper-based catalyst
CN120519901B